Pengendalian Kualitas Menggunakan Metode Six Sigma dan FMEA untuk Mengurangi Reject Material Preform pada Industri AMDK - Alfarizi, Novyantika; Noya, Sunday; Hadi, Yuswono (Teknik Industri Universitas Ma Chung, 2023)
One of the stages of bottled drinking water production at PT X is bottle making using preform material. Preform material is made from PET (Polyethylen Terphtalate). During the production process, there are preform material rejects such as broken bottles, unstable bottle thickness, white preforms, pinched bottles, and white bottles. The total preform material rejects during January to October 2022 amounted to 0.98% or there were 234,504 pcs of preform rejects from the total production of 23,905,322 bottles. The percentage of preform material rejects is above the company standard of 0.5%, so it requires Six Sigma and FMEA methods to reduce these rejects. The proposed improvement recommendations are blowing machine operation checklist form, preform specification form for suppliers, and training schedule form. However, the recommendation that was implemented was the blowing machine operation form checklist because machine malfuction was the main factor causing preform material rejects based on FMEA analysis. The recommendation was implemented for one month in November and succeeded in reducing preform material rejects by an average of 0.86% or there were preform rejects of 298,641 pcs of preforms from a total production output of 34,599.74 bottles during January to November 2022. The final calculation after the implementation of the proposed improvements shows that there is a decrease in the DPMO value from 1961.93 to 1726.26 and an increase in the sigma level value of 4.42 sigma which was previously 4.38 sigma, from this value it shows that the sigma level has increased by 0.04 sigma.